THE INFLUENCE OF WORK ENVIRONMENT AND COMPETENCE ON PERFORMANCE MEDIATED BY JOB SATISFACTION OF EMPLOYEES OF THE ARCHIVES AND LIBRARY OFFICE OF KAPUAS REGENCY - Irawanto; Bella Saputra; Misransyah Akos; M. Heru Budihantho; Semuel Risal (stiatabalong.ac.id, 2024)
Based on the accountability report of the Kapuas Regency Archives and Library Service in 2021, this institution is still not optimal, and the unevenness of archive management and services provided is why this research was conducted. This study aims to determine the effect of work environment and competence on performance mediated by job satisfaction at the Kapuas Regency Archives and Library Service. This study uses a quantitative approach with a sample size of 40 people. Primary data was obtained by distributing questionnaires, and secondary data was obtained from documentation and data available at the research locus. The analysis was carried out in three stages: first, calculating the outer model value; second, calculating the inner model value; and third, testing the hypothesis. Respondents of this study were State Civil Apparatus (ASN) and Non Permanent Employees (PTT) who worked at the Kapuas Regency Archives and Library Office with a total of 40 people. Based on the results of this study, it is proven that the research hypothesis states (H1) that the effect of work environment on job satisfaction is positive and significant, (H2) that the effect of competence on job satisfaction is positive and significant, (H3) that the effect of work environment on performance is positive and insignificant, (H4) that the effect of competence on performance is positive and insignificant, (H5) that the effect of job satisfaction on performance is positive and significant, (H6) that job satisfaction has a positive effect and can mediate the effect of work environment on performance, and (H7) that job satisfaction has a positive effect and can mediate the effect of competence on performance. Keywords: work environment, competence, performance, job satisfaction